Individual and joint contributions of genetic and methylation risk scores for enhancing lung cancer risk stratification: data from a population-based cohort in Germany - Yu, Haixin; Schöttker, Ben; Holleczek, Bernd; Zhang, Yan; Brenner, Hermann (Clinical epigenetics, 2020)
Risk stratification for lung cancer (LC) screening is so far mostly based on smoking history. This study aimed to assess if and to what extent such risk stratification could be enhanced by additional consideration of genetic risk scores (GRSs) and epigenetic risk scores defined by DNA methylation.
Gesehen am 18.08.2020